The Winter Palace and the people : staging and consuming Russia's monarchy, 1754-1917 - McCaffray, Susan Purves (Northern Illinois University Press, 2018)
"In the face of a changing social landscape in their rapidly growing nineteenth-century capital, Russian monarchs reoriented their display of imperial and national representation away from courtiers and toward the urban public. When attacked at mid-century, monarchs retreated from the palace. As they receded, the public claimed the square and the artistic treasures in the Imperial Hermitage before claiming the palace itself. By 1917, the Winter Palace had come to be the essential stage for representing not just monarchy, but the civic life of the empire-nation. What was cataclysmic for the monarchy presented to those who staffed the palace and Hermitage not a disaster, but a new mission, as a public space created jointly by monarch and city passed from the one to the other. This insightful study will appeal to scholars of Russia and general readers interested in Russian history."--Amazon